Model of Implementing Teacher Certification Policy Using The Edward III Approach In Aceh Tamiang District - Nurbaiti (JOLADU: Journal of Language Education, 2023)
This study describes the implementation of teacher certification regulations in Kuala Simpang, Aceh Tamiang District. This analysis uses several factors found by Edward III in the form of communication, resources, disposition, and bureaucratic structure. The purpose of this research is to educate the reader so that the reader is intellectually and morally intelligent. A qualitative descriptive approach is used in this paper. The results found indicate that the process of implementing certification at the Aceh Tamiang education office has not been effective, requiring several obstacles such as a lack of facilities and infrastructure, as well as inconsistent regulations that make it difficult for teachers. This causes teachers to be incapable and do not meet the requirements in completing lesson plans, there are still some teachers who are found to lack discipline and bad attitudes and certification is only considered for personal welfare and gain. Thus it can be said that the certification program has not played an important role in teacher professionalism.